Association between Iron deficiency and hypothyroxinemia in first-trimester pregnant women: A study from a tertiary care hospital - Savitha Vijayakumar; B Madhu; M. Mounika Sree; Mahesh Mahadevaiah; H Basavanagowdappa (Current Medicine Research and Practice)
Background: Iron deficiency (ID) is a common nutritional concern worldwide. Hypothyroidism during pregnancy also has harmful effects on both mother and child, such as post-partum hemorrhage, pre-eclampsia, low-birth weight, pre-term labour and abruptio placenta. Few articles have shown an association between ID and hypothyroidism. Aims: To evaluate the association between hypothyroidism, hypotriiodothyroninemia and ID in pregnant women. Materials and Methods: This cross-sectional study was conducted between January 2017 and June 2019 at JSS Hospital, a Tertiary Care Teaching and Research Hospital attached to JSS Medical College in Mysuru City, South India. Five hundred consecutive pregnant women aged 18–45 years in the first trimester of pregnancy were recruited. A venous blood sample of approximately 5 mL was drawn and sent for analysis of haemoglobin, thyroid-stimulating hormone (TSH), T3, T4, anti-thyroid peroxidase (TPO) antibodies and serum ferritin. T3, T4, TSH, anti-TPO antibody and serum ferritin levels were measured by chemiluminescence for all pregnant women. Correlation and linear regression analyses were performed to determine the association between ID and T3, T4 and TSH levels. Results: Out of 500 women, nine were excluded because of pre-analytical errors; hence, there were 491 pregnant women in the first trimester. Mean values of T3, T4, TSH and ferritin in the study were 1.45 ± 0.72, 9.29 ± 2.53, 2.37 ± 3.17 and 31.54 ± 30.28. There was a positive correlation between serum ferritin and T4 levels, with a correlation coefficient of 0.135. The scatter plot also showed a linear relationship between serum ferritin and T4 levels. There was no significant correlation between serum ferritin, T3 and TSH levels. Linear regression analysis also showed an association between ferritin and T4 levels, with a significance of 0.003. Linear regression analysis was insignificant for TSH, T3 and serum ferritin levels. Conclusion: ID anaemia (IDA) is associated with hypothyroxinemia in pregnant women. Further extensive studies are needed to evaluate the causal association between hypothyroidism and IDA. Iron therapy might improve thyroid parameters in patients with subclinical hypothyroidism and ID without thyroxine, which requires further research.